Does negative parenting behavior lead to later peer victimization? A longitudinal co-twin control study - Oncioiu, Sînziana Ioana; Korde, Amber; Klatzka, Christoph H.; Bowes, Lucy (SAGE PUBLICATIONS LTD, 2025)
Negative parenting behavior is associated with peer victimization. However, we do not know if this association changes across development. It is also unclear whether associations hold after adjusting for genetic factors. Peer victimization and negative parenting behavior were examined using data from TwinLife, a cross-sequential population-based longitudinal study in Germany. The sample comprised 609 reared-together twin pairs from the 5-year-old cohort and 605 twin pairs from the 11-year-old cohort. We used maternal reports of parenting at baseline and child self-reports of peer victimization measured 2 years later. We used a co-twin design among monozygotic twins to control for shared environmental and genetic factors. At the population level, exposure to negative parenting behavior was associated with increased likelihood of peer victimization (5 years old: beta = 0.03, 95% confidence interval [CI] = 0.01 to 0.05; 11 years old: beta = 0.02, 95% CI = 0.01 to 0.03). The strength of the association was similar for participants in both age cohorts. However, the associations between negative parenting behavior and peer victimization did not remain statistically significant after accounting for genetic and shared environmental factors among monozygotic twins (5 years old: beta = -0.01, 95% CI = -0.08 to 0.06; 11 years old: beta = 0.03, 95% CI = -0.04 to 0.09). In exploratory analyses, we found that in early adolescence, monozygotic girls exposed to negative parenting behavior presented higher levels of peer victimization than boys (monozygotic girls: beta = 0.11, 95% CI = 0.03 to 0.19; monozygotic boys: beta = -0.08, 95% CI = -0.19 to 0.02). Our findings suggest that the relationship between negative parenting behavior and children's risk for peer victimization may reflect shared underlying environmental and genetic risks. Our study highlights the importance of using genetically sensitive research designs when considering the role of parenting in the development of children's social relationships.